2021
DOI: 10.3390/molecules26237305
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of Low Dose Dimethyl Sulfoxide on Mitochondrial Function and Oxidative Damage in Cultured Cardiac and Cancer Cells

Abstract: Although numerous studies have demonstrated the biological and multifaceted nature of dimethyl sulfoxide (DMSO) across different in vitro models, the direct effect of “non-toxic” low DMSO doses on cardiac and cancer cells has not been clearly explored. In the present study, H9c2 cardiomyoblasts and MCF-7 breast cancer cells were treated with varying concentrations of DMSO (0.001–3.7%) for 6 days. Here, DMSO doses < 0.5% enhanced the cardiomyoblasts respiratory control ratio and cellular viability relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In adipocytes, for example, DMSO at concentrations ≥1% for 1 h reduced cell viability and accelerated cellular apoptosis by increasing mitochondrial membrane potential and ROS 42 . Elsewhere, in cardiomyoblasts and in breast cancer cells, 3.7% DMSO exposure for 6 days induced apoptosis driven by mitochondrial dysfunction and oxidative stress 44 . Finally, exposure of astrocytes to 5% DMSO for 24 h caused cell viability loss and mitochondrial integrity disruption, membrane potential impairment, ROS production, and subsequent cytochrome C release and caspase‐3 activation 45 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In adipocytes, for example, DMSO at concentrations ≥1% for 1 h reduced cell viability and accelerated cellular apoptosis by increasing mitochondrial membrane potential and ROS 42 . Elsewhere, in cardiomyoblasts and in breast cancer cells, 3.7% DMSO exposure for 6 days induced apoptosis driven by mitochondrial dysfunction and oxidative stress 44 . Finally, exposure of astrocytes to 5% DMSO for 24 h caused cell viability loss and mitochondrial integrity disruption, membrane potential impairment, ROS production, and subsequent cytochrome C release and caspase‐3 activation 45 .…”
Section: Discussionmentioning
confidence: 99%
“… 42 Elsewhere, in cardiomyoblasts and in breast cancer cells, 3.7% DMSO exposure for 6 days induced apoptosis driven by mitochondrial dysfunction and oxidative stress. 44 Finally, exposure of astrocytes to 5% DMSO for 24 h caused cell viability loss and mitochondrial integrity disruption, membrane potential impairment, ROS production, and subsequent cytochrome C release and caspase‐3 activation. 45 Consistent with these previous reports, we demonstrated that DMSO increases intracellular and mitochondrial ROS in NPC in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Natural plant compounds (naringenin [ 3 ], papaverine [ 4 ], polyphenols isolated from Myrciaria trunciflora [ 5 ] or Anneslea fragrans [ 6 ], and seed-derived peptides [ 7 ]), natural compounds also found in animals (melatonin [ 2 , 8 ]), and peptides as well as proteins from Jellyfish venom [ 9 ]. Synthetic compounds, i.e., alkyl thiols [ 10 ], dimethyl sulfoxide [ 11 ], metformin and S63845 [ 12 ], the ruthenium complex [Ru(Phen) 3 ] 2+ [ 13 ], and copper-based compounds—Casiopeinas [ 14 ]. Different formulations, i.e., peptide fractions from germinated soybeans conjugated to Fe 3 O 4 nanoparticles [ 15 ] and astaxanthin microparticles in combination with pentoxifylline [ 16 ].…”
mentioning
confidence: 99%